Preemptive cyclosporin A in immune‐mediated thrombotic thrombocytopenic purpura. (14th November 2022) - Comparon, Celine; Galicier, Lionel; Rebibou, Jean Michel; Coppo, Paul; Benhamou, Ygal
Abstract: Survivors of immune‐mediated thrombotic thrombocytopenic purpura (iTTP) are exposed to clinical relapses when a disintegrin and metalloproteinase with thrombospondin type 1 repeats, member 13 (ADAMTS13) activity decreases during follow‐up. Although preemptive rituximab usually improves ADAMTS13 activity in this context, 15% of patients experience refractoriness or intolerance to rituximab and require alternative strategies. Here, we addressed whether cyclosporine A (CSA) could improve ADAMTS13 activity and prevent clinical relapses in this context. We treated preemptively with CSA 14 iTTP patients who were unresponsive ( n = 11) or intolerant ( n = 3) to rituximab. All patients had a severe ADAMTS13 deficiency (activity <20%) and otherwise in clinical remission. ADAMTS13 activity normalized in almost all patients ( n = 13, 93%), after a median time of 2.5 months [IQR 1–6] following initiation. Median duration of CSA treatment was 17.5 months [IQR 10–34]. ADAMTS13 activity further declined to undetectable values during follow‐up in five patients, but retreatment with rituximab or CSA allowed a recovery in ADAMTS13 activity in three cases. CSA could be stopped durably in two patients, while two others experienced an ADAMTS13 relapse. Severe but reversible side effects requiring cessation of the treatment occurred in two patients. CSA provides high and sustained response rates in patients who are refractory or intolerant to rituximab, with acceptable adverse events.